Resilience of Rubber Farmers' Households Due to Aslide Disaster in the Danau Village, Nalo District, Tantan Merangin Jambi Province - Irwan, Irwan; Zusmelia, Zusmelia; Virginia, Delia; Amelia, Anggun; Siahaan, Kevin William Andri (Future Science / FSH-PH Publications, 2022)
The focus of this study is to analyze the resilience of rubber farmer households due to landslides in the lake village, Nalo Tantan sub-district, Merangin Regency, Jambi Province. This study used a qualitative approach with descriptive type, and the informants of this study were carried out by purposive sampling. The informants of this research are rubber farmer households experiencing pressure from landslides. Data collection methods started from in-depth interviews, observation and document data collection. The unit of analysis in this study is at the household level, namely the rubber farmer household. Data analysis was carried out in several stages, namely data collection, data reduction, data study and drawing conclusions, which were referred to in the Miles and Hubermen model. The results of this study indicate that the household life of rubber farmers is included in the lower middle economy . Rubber farmer households continue to survive driven by the lack of capital to find adequate housing to keep living. The problem found by researchers is that there are no other jobs or other skills owned by rubber farmers. The income of rubber farmers can be seen from the amount or nominal amount of money generated from the sale of rubber. The high and low prices of rubber greatly affect production